PENGARUH MODEL KOOPERATIF INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA MATERI VIRUS KELAS X SMA - Selviana, Lili; Aryati, Eka; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This research aimed to identify the effect of cooperative learning type index card match toward students learning outcomes. The research focused on the material about virus for tenth grade science major. The research applied quasi-experimental method with non-equivalent control group design. Sample in this research was taken through intact group technique, where tenth grade of science 1 as the experimental class and tenth grade of science 2 as the control class. The instrument was a multiple-choice test consisting of 20 questions. The average value of students outcomes at the experimental class was 16.13. Meanwhile, the average for control class was 14.43. Using U Mann-Whitney test, the research obtained -Zcount< -Ztable there was -2.21< -1.96. This value means that there is a significant difference of learning outcomes between students who use cooperative learning type index card match and those who study conventionally. The value of effect size obtained in this research was 0.56 which could be classified medium. It shows us that cooperative learning of type index card match has an effect as much as 21.23% towards students outcomes, especially in the material of virus tenth grade science student.Â Keywords: Cooperative Learning type index card match, learning outcomes, virus